2019
DOI: 10.1590/1807-1929/agriambi.v23n5p341-346
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric responses and tolerance of pomegranate seedlings irrigated with saline water

Abstract: Information on the production of seedlings and initial growth of pomegranate irrigated with saline water is scarce in the Brazilian semi-arid region. The objective of this study was to assess the effect of irrigation water salinity levels on the growth and tolerance of pomegranate seedlings. The experiment was conducted in a greenhouse, located at the Federal Rural University of the Semi-Arid Region, Mossoró, RN, Brazil. A randomized block design with five treatments [electrical conductivities of irrigation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…In Brazil, the crop has aroused the interest of producers, especially in the Northeast region, due to its rapid growth and adaptability to the conditions of the Brazilian semi-arid region, as well as its high market value (Almeida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the crop has aroused the interest of producers, especially in the Northeast region, due to its rapid growth and adaptability to the conditions of the Brazilian semi-arid region, as well as its high market value (Almeida et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This fruit crop shows adequate production suitability in arid and semi-arid regions, and its cultivation can be expanded to regions where the available water has high salt concentrations, because it is relatively tolerant to salt stress, with variations among cultivars (Okhovatian-Ardakani et al, 2010;El-Khawaga et al, 2013). Almeida et al (2019), evaluating the effect of levels of irrigation water salinity on the growth and tolerance of pomegranate seedlings, found that pomegranate was tolerant to the effects of water salinity up to 6.0 dS m -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian Northeast show low rainfall and suffers from water scarcity and high salt content in soils and water sources used for irrigation. Such conditions severely affect the development of crops in the region (Almeida et al, 2019). The high salt content in water and soil causes salt stress in plants which may disturb growth and development, by mainly affecting the photosynthetic apparatus (Cavalcante et al, 2019), resulting in biomass production losses.…”
Section: Introductionmentioning
confidence: 99%